We defined the algebraic multiplicity of a matrix $A$ with eigenvalue $\lambda$ to be the largest integer $r$ such that $(x-\lambda)^r$ divides the characteristic polynomial of $A$.

I would like to know if that is the same as the minimal integer $s$ so that the kernel of $(A-\lambda I)^s$ is the same as the kernel of $(A-\lambda I)^{s+1}$. I am not really sure if that is true and how one can prove that. And does $(x-\lambda)^s$ divide the minimal polynomial then?

Could you clear up this question for me? If possible, is there a proof for this claim without using the Jordan Normal Form? I know about the decomposition in (invariant) generalized eigenspaces though.

Thank you!

  • 1
    $\begingroup$ No, this is not true. For $A = I_n$, the only eigenvalue is $\lambda = 1$, and the characteristic polynomial is $(x - 1)^n$, so the algebraic multiplicity is $n$, but $A - I_n = 0$, so $\ker (A - I_n) = \ker ((A - I_n)^2)$, and hence the minimal integer $s$ is $1$. $\endgroup$ – Travis Willse Jun 27 '18 at 2:52
  • 2
    $\begingroup$ It is true that $(x - \lambda)^s$ divides the minimal polynomial of $A$, and is in fact the largest power of $(x - \lambda)$ which divides the minimal polynomial. In terms of the Jordan form, $s$ is the size of the largest Jordan block associated with $\lambda$. $\endgroup$ – Ben Grossmann Jun 27 '18 at 6:33

The minimal integer $s$ such that $\ker (A -\lambda I)^s = \ker (A - \lambda I)^{s+1}$ is precisely the largest power of $x-\lambda$ which divides the minimal polynomial of $A$. This is in general $\le $ than the algebraic multiplicity of $\lambda$.

Recall that in general holds $\ker T \subseteq \ker T^2 \subseteq \ker T^3 \subseteq \cdots$ and that if $\ker T^m = \ker T^{m+1}$ then $\ker T^m = \ker T^{n}, \forall n \ge m$.

The rest follows from this lemma:

Let $A : V \to V$ be a linear map on a finite-dimensional complex vector space $V$ with the eigenvalues $\{\lambda_1, \ldots, \lambda_r\}$. Then a polynomial $p(x) = (x-\lambda_1)^{m_1}\cdots (x-\lambda_r)^{m_r}$ annihilates the map $A$ if and only if $$V = \ker (A-\lambda_1 I)^{m_1} \,\dot+\,\cdots \,\dot+\,\ker(A-\lambda_r I)^{m_r}$$

The direction $\impliedby$ is more-less obvious, and for $\implies$ you can use the partial fraction decomposition of $\frac1{p(x)}$. Note that this sum is always direct, i.e. we have $\ker (A-\lambda_i I)^{m_i} \cap \ker (A-\lambda_j I)^{m_j} = \{0\}, \forall i \ne j$ so you just need to prove that the sum is equal to $V$.

Let $\mu_A(x) = (x-\lambda_1)^{s_1}\cdots (x-\lambda_r)^{s_r}$ be the minimal polynomial of $A$. Then by the lemma we conclude $$V = \ker (A-\lambda_1 I)^{s_1} \,\dot+\,\cdots \,\dot+\,\ker(A-\lambda_r I)^{s_r}$$

Let $m_i\ge s_i$. Then clearly $(x-\lambda_1)^{m_1}\cdots (x-\lambda_r)^{m_r}$ also annihilates $A$ so $$V = \ker (A-\lambda_1 I)^{m_1} \,\dot+\,\cdots \,\dot+\,\ker(A-\lambda_r I)^{m_r}$$

Now $$\sum_{i=1}^r \dim\ker (A-\lambda_i I)^{m_i} = \dim V = \sum_{i=1}^r \dim\ker (A-\lambda_i I)^{s_i}$$ implies $\dim\ker (A-\lambda_i I)^{m_i} = \dim\ker (A-\lambda_i I)^{s_i}$ so $\ker (A-\lambda_i I)^{m_i} = \ker (A-\lambda_i I)^{s_i}$ for all $i = 1,\ldots, r$.

On the other hand, if $k_i \le s_i$ and we assume $\ker (A - \lambda I)^{k_i} = \ker (A - \lambda I)^{s_i}$, then we have

$$V = \ker (A-\lambda_1 I)^{k_1} \,\dot+\,\cdots \,\dot+\,\ker(A-\lambda_r I)^{k_r}$$

so the lemma implies that the polynomial $p(x) = (x-\lambda_1)^{k_1}\cdots (x-\lambda_r)^{k_r}$ annihilates $A$. Hence the minimal polynomial divides $p $ so $k_i = s_i$ for all $i = 1, \dots, n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.